Implications of Inflammatory States on Dysfunctional Immune Responses in Aging and Obesity - Thomas, Alyssa L.; Alarcon, Pablo C.; Divanovic, Senad; Chougnet, Claire A.; Hildeman, David A.; Moreno-Fernandez, Maria E. (Frontiers in Aging, 2021)
Aging and obesity are two conditions characterized by chronic, low-grade inflammation. While both conditions are also associated with dysfunctional immune responses, the shared and distinct underlying mechanisms are just starting to be uncovered. In fact, recent findings have suggested that the effects of obesity on the immune system can be thought of as a state of accelerated aging. Here we propose that chronic, low-grade inflammation seen in obesity and aging is complex, affects multiple cell types, and results in an altered basal immune state. In aging, part of this altered state is the emergence of regulatory immune populations that lead to further immune dysfunction in an attempt to reduce chronic inflammation. While in obesity, part of the altered state is the effect of expanding adipose tissue on immune cell function. Thus, in this review, we compare, and contrast altered immune states in aging and obesity and discuss their potential contribution to a shared clinical problem- decreased vaccine responsiveness.